Field testing of recombinant subunit vaccines against Teladorsagia circumcincta in lambing ewes demonstrates a lack of efficacy in the face of a multi-species parasite challenge - Nisbet, Alasdair J.; McNeilly, Tom N.; Price, Daniel R. G.; Bartley, Yvonne; Oliver, Margaret; McBean, Dave; Andrews, Leigh; Mitchell, Gillian; Duncan, Rachael; Brocklehurst, Sarah; Kenyon, Fiona (Frontiers in Parasitology, 2024)
We previously demonstrated efficacy of an 8-antigen recombinant subunit vaccine against a single species homologous Teladorsagia circumcincta challenge in lambs and in lambing ewes in pen trials. We subsequently demonstrated efficacy of a simplified, 2-antigen, version of this vaccine in lambs in pen trials. Here, we test both vaccines in lambing ewes in a field setting.In the work presented here, 12 adjacent plots were seeded with a mixed infection of several common species of parasitic nematodes of sheep in temperate regions, including T. circumcincta. Ewes (n = 144), in groups of 12, grazed for 2 years on these plots and, in the first year, six of these groups of ewes were vaccinated with a 2-antigen prototype vaccine against T. circumcincta prior to mating and then again prior to lambing. In the following year these ewes were immunized again, this time with the 8-antigen prototype vaccine against T. circumcincta prior to mating and then prior to lambing. Throughout both seasons antigen-specific serum antibody levels in ewes and faecal worm egg counts (FEC) in ewes and their lambs were monitored, along with nematode species diversity at lambing.Immunised ewes produced elevated serum antibody levels to each of the vaccine antigens following immunisation but their FEC levels were not statistically significantly impacted by vaccination with either vaccine. FEC levels were also not impacted in lambs co-grazing the pastures with these immunized ewes. Nematode species diversity was not significantly impacted by vaccination in either year.The immunosuppressive effects of co-infecting gastrointestinal nematodes, the absence of vaccine cross-protection against co-infecting species and the influence of the periparturient relaxation in immunity probably all contributed to the inability of either vaccine to protect against T. circumcincta infection in field trials in the work presented here.